DIGITAL MARKETING DALAM MENINGKATKAN PENJUALAN PRODUK PIA MAHEN - Baswedan, Fauzi; Utomo, Zulkifli Arizalu Satrio; Rochmaniah, Ainur; Febriana, Poppy (LP2M Universitas Bina Bangsa, 2025)
The purpose of implementing this community service is a form of responsibility from CSR (corporate social responsibility) to the surrounding community. This time the community service is focused on Pia Mahen MSMEs engaged in snacks, the presence of MSMEs also has a positive impact on improving the economy in Indonesia. The method used to carry out community service is by using 3 stages, starting from the pre-production stage which contains the search for problems that are being experienced by the resource persons, during production, namely the process of community service by carrying out various programs that have been formed, and post-production, namely the assessment stage of the success of the community service process that has been implemented. The selection of this method is considered helpful to classify the order that will be carried out for this community service. The result obtained from this community service is that there is an increase in followers and posts on Pia Mahen's Instagram and TikTok accounts, with the creation of interactive and creative content, thereby expanding the marketing reach of Pia Mahen's products. Based on the community service that has been carried out, it is understood that participation in marketing strategies with online media is very influential and has a significant impact